Bioactive pyrones and flavonoids from Cryptocarya ashersoniana seedlings - Ricardo, MAG; Andreo, M. A.; Cavalheiro, Alberto José [UNESP]; Gamboa, Ian Castro [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Silva, DHS (Arkat Usa Inc, 2004)
The bioassay directed fractionation of the EtOH extract from leaves of Cryptocarya ashersoniana seedlings led to the isolation of two flavonol glucosides: iso-quercitrin and hyperin, which exhibited free radical scavenging activity towards DPPH (IC50 34.4 muM and 32.7 muM, respectively) and were compared to standard compounds rutin (IC50 27.0 muM) and catechin (IC50 41.4 muM). Investigation of extracts from the seedlings roots and stems afforded one antifungal styrylpyrone: goniothalamine, and two dihydropyrones: 6-propyl-5,6-dihydro-2-pyrone and the new 6-[(4'-ethyl-9'-oxabicyclo[3.3.1]non-6'-en-3'-yl)methyl]-5,6-dihydro-2H-pyran-2-one, which had its structure determined by detailed analysis of MS and NMR data, including 2D experiments.
Keywords: Cryptocarya ashersoniana; Lauraceae; pyrone; flavonoid; antioxidant; free radical scavenger; DPPH